Diagnostic value of the lower leg muscle stiffness in professional skiers with medial tibial stress syndrome: A retrospective shear wave elastography study - Akaras, E.; Aktas, B. S.; Cankaya, B. Y.; Oztop, B.; Abbasguliyev, H.; Kishal, N. F.; Yagiz, G. (Physical Therapy in Sport, 2026)
Objectives This study aims to assess the diagnostic value of tibialis anterior (TA) and gastrocnemius muscle elasticity using shear wave elastography (SWE) in professional skiers diagnosed with medial tibial stress syndrome (MTSS).